La experiencia de tener un hermano en niños de ocho a diez años - Tagliabue Ganoza, Regina (2012)
This research aims to describe and understand, from a psychoanalytic point of view and theoretical framework, the experiences of having a sibling for the first time among kids aged eight to ten years old. To do this, from a cualitative paradigm, I have explored eight cases of children in this situation. The data collection process was performed on two individual conversations with each kid. On the first conversation some test sheets were taken from “Adventures of Blackfoot” as a motivator for generating stories. On the second one the children were asked to make a drawing of “siblings” and a story drawn from it. A conversation with the parents of each child was also an research instrument to gather information necessary about their development process and to explore the child reactions towards the experience of having a sibling for the first time. The discussions with the parents and the children were recorded and transcribed. The results have been discussed from the theoretical framework and from some research from a clinical perspective and with children of other ages, as our research is unique in relation to the subject and the target population.